The Influence of the Korean Wave on Culinary Tourism Development in Myeongdong, Seoul in 2020 - Linda Ugi; Styani Dwi Rahmatika Jumadi; Andika Drajat Murdani (Penerbit Goodwood, 2025)
Purpose: This study examines the influence of the Korean Wave (Hallyu) on culinary tourism interest in Myeongdong, Seoul, focusing on the “K-drama food pilgrimage” phenomenon and its evolution during the COVID-19 pandemic in 2020. Methodology: A qualitative descriptive approach was applied using literature review and secondary data analysis. Data sources include academic publications, Korea Tourism Organization reports, and documented culinary tourism trends in Myeongdong. Results: Findings show that Hallyu significantly increased international tourists’ interest in Korean cuisine, particularly through media-driven food experiences. However, the COVID-19 pandemic caused a severe decline in culinary tourism, with an 85% drop in international visitors and a 31% increase in shop vacancies in Q3 2020, while also accelerating digital transformation and business innovation among food entrepreneurs.Conclusions: The Korean Wave plays a central role in shaping culinary tourism demand in Myeongdong and demonstrates resilience through adaptation and digitalization during crisis conditions.Limitations: This study relies on secondary data and lacks primary empirical validation from tourists or business actors, which may limit contextual depth.Contributions: This research contributes to culinary tourism literature by explaining the intersection of cultural soft power and crisis-driven digital adaptation in a global tourism destination.